A Most Fragile Art Object: Interpreting and Presenting the Strolling Garden of the Villa Arianna, Stabiae - Howe, Thomas N. (Actual Problems of Theory and History of Art, 2018)
In 2007 the Superintendancy of Pompei and the Restoring Ancient Stabiae Foundation uncovered an enormous formal garden in the so-called Villa Arianna at Stabia, near Pompeii, some 113 m long, in an excellent state of preservation. The soil surfaces were as excellently preserved as they had been on the morning of the 24th of August, 79 CE: the surfaces of what had been grassy walkways (ambulationes); planting beds for shrubs (viridia); and lines of trees of many species. Root cavities preserved root forms down to the size of hair roots.From 2007 to 2012 the Restoring Ancient Stabiae Foundation and its many collaborators assumed the final excavation and study of the garden surface, which is in final stages of publication. The result is that the study of this most ephemeral of archaeological art objects — an ancient garden — has demonstrated that highly innovative developments in the Later Republic and Early Empire in architecture, painting and poetry parallel and are paralleled by innovations in garden design. Without the garden, one cannot interpret the architecture.Analysis of the garden surfaces, especially by Kathryn Gleason and her team from Cornell, revealed that the beds of shrubs are the first archaeological evidence ever found for the type of miniaturized rustic garden seen in the famous fresco of the Villa of Livia at Prima Porta. The rows of trees are all formally aligned but of different species, like a zoological gazetteer of empire. The arrangement of plants creates the same type of “differential cross-axial” experience of near space and distant views that architects were creating in the architecture of the early Empire. Hence the garden is planted with the professional skill for special manipulation of space that heralds the arrival of the professional landscape architect (topiarius). This art was not only the manipulation of space but also of the people who moved through those spaces. The elite in the Roman mansion normally moved through wide spaces which connected to one another, and the servile class moved through corridors and stood semi-invisibly in the shadows. But our analysis, illustrated by digital reconstructions and videos, shows that the large formal garden of the Villa Arianna was meant to be walked in, and its design allowed for all sorts of viewing, of encounters, and of avoidance of encounters. This was a place where people of great power and privilege came to interact, largely out of view of conspectus populi, but to interact, under the control of the host/ dominus and hostess/domina.Without this knowledge about the garden, the interpretation and visit to the great villas of the Bay of Naples is like visiting an empty, lifeless shell. This paper will present non-destructive approaches to recreating much of the effect of this garden that is being proposed by the Restoring Ancient Stabiae Foundation, whose mission is to assist the Superintendancy of Pompei in creating a large archaeological park on the site of the villas of Stabiae.
Keywords: Roman villas; Stabiae; Villa Arianna at Stabia; Villa of Livia; Prima Porta; the Restoring Ancient Stabiae Foundation; Superintendancy of Pompei; Gulf of Naples; villa maritima; archaeological park; conservation of archaeological sites; garden and park landscape art; landscape design; panoramic villas/views; architecture of Classical antiquity; antique gardens; Roman gardens